Uptake of community-based differentiated antiretroviral therapy service delivery and associated factors among people living with HIV in Ethiopia: a multicenter cross-sectional study - Merid, Fasika; Toma, Temesgen Mohammed; Anbesie, Abraham; Guyo, Tamirat Gezahegn (Frontiers in Public Health, 2024)
Background: The 95-95-95 targets require an efficient and innovative person-centered approach, community-based differentiated service delivery (DSD), to improve access to human immunodeficiency virus (HIV) services and reduce burdens on the health system. Hence, this study aimed to assess the uptake of the community-based DSD models and associated factors among people living with HIV (PLHIV). Methods: A multicenter cross-sectional study was conducted among PLHIV in public health facilities of South Ethiopia. The collected data was entered into EpiData version 3.1 and exported to Stata version 14 for further analysis. In bivariable logistic regression analysis variables with p-value ≤0.25 are included in multivariable logistic regression analysis. P-value < 0.05 was used to identify statistically significant factors. Results: Among 381 stable PLHIV, 55.91% were females. The median age (interquartile range) was 40 years . The uptake of community-based DSD models was 19.16%. Residence and disclosure were the independent factors significantly associated with the uptake of community-based DSD models. Conclusion: One out of five PLHIV uptakes the community-based DSD models. Improvement in uptake is needed in the resource-limited country of Ethiopia's health care system.